Main factors that affect the low academic performance of the english subject from 9th grade students, in Daniel Octavio Crespo High School, Concepcion, Bugaba Chiriquí, 2013 - Guerra, Yenisbeth (UDELAS, 2013)
For many years, the low academic performance has been a problematic in the education that is reflected in the grades of the students. This issue has become very important in the educational field, where teachers use different methodologies of teaching and different activities to figure out the possible solution.